2016
DOI: 10.1242/bio.016758
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PI3K signaling prevents aminoglycoside-induced hair cell death in the murine cochlea

Abstract: Loss of sensory hair cells of the inner ear due to aminoglycoside exposure is a major cause of hearing loss. Using an immortalized multipotent otic progenitor (iMOP) cell line, specific signaling pathways that promote otic cell survival were identified. Of the signaling pathways identified, the PI3K pathway emerged as a strong candidate for promoting hair cell survival. In aging animals, components for active PI3K signaling are present but decrease in hair cells. In this study, we determined whether activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 68 publications
(83 reference statements)
3
24
0
Order By: Relevance
“…Under this interpretation, our work extends these findings in several important ways. First, we prove that activation in supporting cells alone is sufficient to promote hair cell survival, as the previous studies used either pharmacological inhibitors, deleted PTEN in both supporting cells and hair cells, or both (57,58). Second, our work indicates that the induction of CA-ERBB2, and/or its potential effector PI3K, can rescue adult hair cells from a noise-induced death.…”
Section: Discussionsupporting
confidence: 61%
“…Under this interpretation, our work extends these findings in several important ways. First, we prove that activation in supporting cells alone is sufficient to promote hair cell survival, as the previous studies used either pharmacological inhibitors, deleted PTEN in both supporting cells and hair cells, or both (57,58). Second, our work indicates that the induction of CA-ERBB2, and/or its potential effector PI3K, can rescue adult hair cells from a noise-induced death.…”
Section: Discussionsupporting
confidence: 61%
“…We previously showed that activation of PI3K signaling could promote hair cell survival (Jadali and Kwan, 2016). We wanted to extend our findings and determine if activation of the PI3K signaling can promote supporting cell survival in the cochlea when subjected to ototoxic damage.…”
Section: Resultsmentioning
confidence: 99%
“…However, Pten ablation in NSE in the same Atoh1-Cre mice did not cause hearing loss in mice (34). Pten knockout in hair cells was recently reported to prevent gentamicin-induced hair cell death (35). To explain this discrepancy, we determined the expression levels of downstream targets of Pten in Pten-cKO (Pten gene inactivated by Atoh1-Cre) cochleae.…”
Section: Inactivation Of Mtorc1 Signaling In Nse Alleviates Arhlmentioning
confidence: 87%